Navigating Sustainability: The Role of Consumer Psychology in Shaping Sustainable Behavior - Enginkaya, Ebru; Saglam, Munise Hayrun (SAGE PUBLICATIONS INC, 2025)
The gap between what consumers say and do threatens the effectiveness of sustainability initiatives. An explanatory-sequential mixed-methods design modeled survey data from 410 Generation Y consumers. We unpacked the statistics through 12 in-depth interviews to probe the psychological levers that could close this gap. A conceptual framework-melding the Value-Belief-Norm theory, the Norm Activation Model, and the Theory of Planned Behavior-posited that Environmental Concern (EC) and the socio-moral emotions of Consumer Guilt (CG) and Ascription of Responsibility (AR) shape Sustainable-Consumption Behavior (SCB) via Perceived Consumer Effectiveness (PCE), with Awareness of Consequences (AC) as a theorized catalyst. PLS-SEM confirmed the framework: EC was associated with SCB (beta = .75); CG (beta = .32); and AR (beta = .42) boosted PCE; PCE, in turn, mediated the EC -> SCB pathway (indirect beta = .15). AC moderated the EC -> PCE link (beta = .22), indicating that concrete knowledge intensifies the sense of personal impact. Thematic analysis corroborated and enriched these findings, surfacing five themes-Concern-Action Gap, Empowered by Impact, Guilt as Moral Driver, Owning the Problem, and Awareness as Catalyst-that mapped neatly onto the SEM paths. Drawn from educated, urban Turkish Gen-Y consumers, this convenience sample allows analytical transfer to similar emerging-economy groups but not statistical generalization. The innovation of this study lies in its integration of three psychological theories into a unified model that is theoretically grounded and practically predictive, bridging emotional, cognitive, and behavioral drivers of sustainable consumption. Pairing vivid consequences with personal-impact feedback most effectively turns EC into lasting pro-environmental behavior.
Keywords: sustainable consumption behavior; environmental concern; consumer guilt; perceived consumer effectiveness; ascription of responsibility; awareness of consequences; NORM ACTIVATION MODEL; PLANNED BEHAVIOR; CONSUMPTION BEHAVIORS; GREEN; AWARENESS; GUILT; SELF; PRIDE; RESPONSIBILITY; Social Sciences - Other Topics